Generational Differences in Purchase Intentions: A Systematic Review of Influencing Factors and Theoretical Frameworks - Tussi Sulistyowati1; Pardomuan Pardosi; Khairil Anwar; Agtovia Frimayasa; Irwin Sukrisno Sugeng (AKADEMI TEKNIK ADI KARYA, 2025)
This study is a qualitative descriptive study based on an SLR using the SPAR-4-SLR protocol to comprehend the contribution of generational differences to consumer purchase intentions. The review incorporates quantitative studies published between 2020 and 2024 and discusses the shopping behavior of Baby Boomers, Generation X, Millennials (Generation Y), and Generation Z. Out of a total of 2,945 Scopus documents, 29 articles were selected through a systematic study identification, data extraction, and thematic analysis based on three research questions. The findings reveal that Generation Z is impacted most by emotional connection, fear of missing out (FOMO), and sustainability values; Millennials by digital engagement, experiential consumption, and personal attitudes; Generation X by product quality and brand trust; and Baby Boomers by product performance and long-term trust. Mediating and moderating forces such as consumer trust, environmental awareness, digital engagement, and self-efficacy also explain these generational differences. Several conceptual models—spanning behavioral, psychological, and social realms—describe the intricacy of purchase intentions and the influence of technology and generational identity. The study presents managerial implications for marketers and companies in creating specific strategies, products, and communication for each generation. Future studies need to look at cultural and contextual variations, observe generational behavior longitudinally, and examine the influence of the newest and newest technologies, like virtual reality and AI-powered sites, on the choice of consumers.